Commit 73eb32bd1f2c452b546f50522ac60cd40483cd7f

Authored by Dany Dumont
1 parent deeb83a3
Exists in master and in 1 other branch snow

Suite du bug fix precedent

src/extras/bio/bio_gsj.F90
@@ -230,7 +230,6 @@ @@ -230,7 +230,6 @@
230 endif 230 endif
231 231
232 232
233 -900 format (a,f8.5)  
234 901 format (f8.5) 233 901 format (f8.5)
235 234
236 ! Conversion from day to second 235 ! Conversion from day to second
@@ -620,12 +619,12 @@ @@ -620,12 +619,12 @@
620 fac4 = hmratio**0.25 619 fac4 = hmratio**0.25
621 620
622 ! Autotroph metabolic rate 621 ! Autotroph metabolic rate
623 - amr1 = max(0.0,ca1*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )  
624 - amr2 = max(0.0,ca2*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac3) 622 + amr1 = max(0d0,ca1*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )
  623 + amr2 = max(0d0,ca2*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac3)
625 624
626 ! Heterotroph metabolic rate 625 ! Heterotroph metabolic rate
627 - hmr1 = max(0.0,ch1*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )  
628 - hmr2 = max(0.0,ch2*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac4) 626 + hmr1 = max(0d0,ch1*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )
  627 + hmr2 = max(0d0,ch2*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac4)
629 else 628 else
630 amr1 = 1.0 629 amr1 = 1.0
631 amr2 = 1.0 630 amr2 = 1.0
src/extras/bio/bio_ismer.F90
@@ -602,12 +602,12 @@ @@ -602,12 +602,12 @@
602 fac4 = hmratio**0.25 602 fac4 = hmratio**0.25
603 603
604 ! Autotroph metabolic rate 604 ! Autotroph metabolic rate
605 - amr1 = max(0.0,ca1*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )  
606 - amr2 = max(0.0,ca2*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac3) 605 + amr1 = max(0d0,ca1*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )
  606 + amr2 = max(0d0,ca2*0.25*exp(Ea/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac3)
607 607
608 ! Heterotroph metabolic rate 608 ! Heterotroph metabolic rate
609 - hmr1 = max(0.0,ch1*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )  
610 - hmr2 = max(0.0,ch2*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac4) 609 + hmr1 = max(0d0,ch1*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0))) )
  610 + hmr2 = max(0d0,ch2*0.25*exp(Eh/(kBeV*T0**2)*(T(ci)/(1+T(ci)/T0)))/fac4)
611 else 611 else
612 amr1 = 1.0 612 amr1 = 1.0
613 amr2 = 1.0 613 amr2 = 1.0